Ekologi Sunnah: Praktik Makanan Nabi antara Rasionalitas Lingkungan dan Imitasi Simbolik dalam Islam Global: Ekologi Sunnah: Praktik Makanan Nabi antara Rasionalitas Lingkungan dan Imitasi Simbolik dalam Islam Global - Sita Acetylena; Moh. Nadhif (LPPI Universitas Al-Qolam Malang, 2026)
Prophetic dietary practices are widely emulated across Muslim societies as part of the living tradition of the Sunnah. However, the global transmission of these practices often occurs beyond the ecological and socio-environmental context in which they originally emerged. This study situates the question of prophetic food practices particularly the tradition of breaking the fast with dates within a broader debate on the relationship between religious tradition, environmental rationality, and symbolic religious expression in contemporary Islam. The purpose of this study is to reinterpret prophetic dietary practices through the conceptual lens of the “Ecology of Sunnah,” a framework that examines how the practices of the Prophet were embedded within specific environmental conditions of the Arabian desert and how their meanings transform when reproduced in different ecological contexts. Employing a qualitative conceptual approach grounded in socio-anthropological analysis of Islamic practices, the study draws upon theoretical insights from scholars such as Clifford Geertz, Pierre Bourdieu, and Talal Asad to analyze how religious practices travel and acquire symbolic meanings in new cultural environments. The findings suggest that prophetic food practices historically reflected ecological rationality such as the nutritional efficiency of dates in arid desert conditions, but in many contemporary Muslim societies these practices are increasingly reproduced as symbolic markers of religious identity rather than contextually adapted wisdom. This transformation reflects a broader shift from contextual rationality to performative imitation within globalized Islam. The study concludes that understanding the Sunnah through an ecological and contextual perspective offers a more holistic interpretation of prophetic traditions and provides an important framework for rethinking how Islamic practices can be meaningfully contextualized in diverse environmental and cultural settings. Key words: ecology of sunnah; environmental rationality; global islam; prophetic food practices; symbolic imitation